(NkONCERTNYE \T@DY DLQ FAGOTA SO^(B.26 (NTETRADX (BIIs (NMUZYKA(B.(NkONCERTs - (Nl(B.(NmILXDE(B.s; (NwALERIJ pOPOW(B.s (NREDAKTORs ((NmOSKWAs (NmOSKOWSKAQ KONSERWATORIQs, 2008)
(NiMQ l@DWIGA mILXDE IZWESTNO FAGOTISTAM WSEGO MIRA (B.(NnA EGO \T@DAH U^ATSQ KAK L@BITELI(B,(NTAK I ISPOLNITELI(B-(NPROFESSIONALY(B.s
Keywords: (NfAGOTs